Give farmland a boost but keep our natural heritage intact - Abd Razak, Dzulkifli (2004)
THE 2004 election is a "thinking election", according to Royal Professor Ungku Aziz (Sunday Mail, March 14) and his assessment is both frank and fair. Malaysia has been playing host to major environmentalrelated forums for almost the entire month of February. For two weeks ending on Feb 20, Malaysia hosted the Seventh Meeting of the Conference of Parties (COP7) to the Convention on Biological Diversity (CBD). And Friday marked the end of the First Meeting of the Parties to the Cartegena Protocol on Biosafety (MOP1) which began on Feb 23. The protocol was adopted as a supplement to the CBD in 2000.